The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9nr00525k
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous MXene monolayer assembly at the liquid–air interface

Abstract: Here we report on the spontaneous assembly of Ti3C2Tx MXene flakes into monolayer films at the liquid–air interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The self-assembly of Ti 3 C 2 T x MXene flakes at the air−water interface into a high-quality film was demonstrated by Petukhov et al 156 The behavior of the MXene flakes in their Langmuir monolayer depend on the pH condition of the subphase. The MXene flakes with negative charges form a thin layer with 1.5 nm thickness at pH > 4, but the thin layer includes coordinated anions to form a Br − /Ti 3 C 2 T x /subphase layer.…”
Section: ■ For Applicationsmentioning
confidence: 99%
“…The self-assembly of Ti 3 C 2 T x MXene flakes at the air−water interface into a high-quality film was demonstrated by Petukhov et al 156 The behavior of the MXene flakes in their Langmuir monolayer depend on the pH condition of the subphase. The MXene flakes with negative charges form a thin layer with 1.5 nm thickness at pH > 4, but the thin layer includes coordinated anions to form a Br − /Ti 3 C 2 T x /subphase layer.…”
Section: ■ For Applicationsmentioning
confidence: 99%
“…The Ti 3 C 2 T x hydrogel with locally oriented structure displayed a moderate steam generation rate of 1.34 kg m –2 h –1 under a light intensity of 1 kW m –2 (1 sun illumination), which is in line with the performance reported for the Ti 3 C 2 T x -based porous evaporator. However, the Ti 3 C 2 T x hydrogel with a vertically aligned microchannels structure showed a much higher evaporation rate, and the highest value based on the projected area was observed in the hydrogel without a disordered “cap” region (1.90 kg m –2 h –1 ). The “cap” structure was formed during the freezing process, in which the accumulation of Ti 3 C 2 T x nanosheets at the liquid–air interface resulted in the formation of the densified structure that impedes the water transport (Figure S13). Herein we removed the cap structure in the Ti 3 C 2 T x frozen gel, and after thawing in protic acid, pristine Ti 3 C 2 T x hydrogels without a cap were prepared (Figure S14).…”
Section: Results and Discussionmentioning
confidence: 99%
“…At a liquid-vapor interface, Ti 3 C 2 T x MXene flakes spontaneously assemble into monolayer films. An XRR and GIXF investigation showed that both the structure of the layers and assembly kinetics depend on the pH of the solution [191]. Graphene oxide is another type of 2DM with increasing interest as a precursor for graphene based materials and as sensors, batteries, etc.…”
Section: Liquid Interfacesmentioning
confidence: 99%